Preliminary pharmacological activity of the methanolic extract of Premna integrifolia barks in rats - Hajera Khatun (Avicenna Journal of Phytomedicine, 2014)
Objective: Premna integrifolia Linn (Family: Verbenaceae) synonym of Premna serratifolia has tremendous medicinal value. Preliminary pharmacological studies were performed on the methanolic extract of Premna integrifolia (MEPI) bark to investigate neuropharmacological, analgesic, and anti-inflammatory activities. Materials and methods: Neuropharmacology study was done by open field and hole cross test whereas acetic acid writhing test and formalin induced pain was done for analgesic activity of MEPI. Carrageenan induced inflammatory model was considered for anti-inflammatory activity evaluation.   Results: A statistically significant (p